Conocimiento y uso de anticonceptivos entre los jóvenes mexicanos. El papel del género - Casique, Irene (El Colegio de México A.C., 2011)
Using data from the National Survey on Violence during Courtship, undertaken in 2007 on young Mexicans aged 15 to 24, the author explores the levels of contraceptive knowledge and use in the context of courtship. This analysis seeks to prove the role played by the various socio-demographic characteristics of young people in contraceptive knowledge and use, with particular emphasis on the role of gender.In general, significant differences are observed between “ever use” of contraceptives and factors associated with condom use in relations with one’s current partner. Contraceptive use appears to be positively associated in both men and women with more favorable socio-economic conditions, greater contraceptive knowledge and a greater number of sexual partners (only among men). Among women, being a student also encourages contraceptive use. However, when characteristics of the courtship are incorporated and the analysis is circumscribed by the frequency of condom use in sexual relations with the current partner, objective relations become less important while certain more subjective features of the relationship become more important. These include: age difference between the partners (for men and women), duration of the courtship (for women), who decides when and how to have sex (for men), support provided by the partner (men only) and attitude towards gender roles (in the case of men) and the presence of emotional violence (for men) and physical violence.